2022
DOI: 10.4149/bll_2022_020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the predictive values of CRP, CRP/albumin, RDW, neutrophil/lymphocyte, and platelet/lymphocyte levels in determining the severity of acute pancreatitis in patients with acute pancreatitis according to the BISAP score

Abstract: BACKGROUND: In our study, it was aimed to fi nd out whether it would be possible to determine the disease severity by comparing the values of red cell distribution width (RDW), c-reactive protein (CRP), CRP/albumin, neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) in patients with acute pancreatitis according to Bedside Index of Severity in Acute Pancreatitis (BISAP) scores at the time of admission. METHODS: Five hundred patients diagnosed with acute pancreatitis were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…They also found that the ratio predicted increased hospital and ICU length of stay. Similar conclusions were drawn by Karabuga et al, who analyzed this relationship of severity using the BISAP score [ 11 ]. They found that for a cut-off of 0.0015, the ratio was 71.43% sensitive and 70.88% specific for predicting severe acute pancreatitis.…”
Section: Reviewsupporting
confidence: 83%
See 2 more Smart Citations
“…They also found that the ratio predicted increased hospital and ICU length of stay. Similar conclusions were drawn by Karabuga et al, who analyzed this relationship of severity using the BISAP score [ 11 ]. They found that for a cut-off of 0.0015, the ratio was 71.43% sensitive and 70.88% specific for predicting severe acute pancreatitis.…”
Section: Reviewsupporting
confidence: 83%
“…All three studies used recognized scoring systems as the standard against which the performance of the CRP/albumin ratio was evaluated; these scoring systems included the Ranson, Atlanta, and BISAP scoring systems. A positive correlation was found between the CRP/albumin ratio at admission and the development of subsequent severe acute pancreatitis in these studies (Tables 2-3) [9][10][11]. The use of the inflammatory ratio involving CRP and prealbumin (PALB) for prognostic purposes can be traced back to 1998 when Pinilla et al established a strong correlation between CRP/PALB with severe organ dysfunction in patients with sepsis [13].…”
Section: Reviewmentioning
confidence: 74%
See 1 more Smart Citation
“…6 In order to predict the prognosis, studies on albumin, white blood cell (WBC), and C-reactive protein (CRP) were performed in patients with pancreatitis. [7][8][9] Hematological parameters have been the subject of studies on acute pancreatitis and many other inflammatory diseases. 2,9 Red cell distribution width (RDW), which may increase due to inflammation, ischemia, and hypoxia, is a measure of the mean corpuscular/erythrocyte volume calculated using the standard deviation of erythrocyte volume heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Hematological parameters have been the subject of studies on acute pancreatitis and many other inflammatory diseases. 2,9 Red cell distribution width (RDW), which may increase due to inflammation, ischemia, and hypoxia, is a measure of the mean corpuscular/erythrocyte volume calculated using the standard deviation of erythrocyte volume heterogeneity. 10,11 Some studies have previously been conducted to evaluate the association of RDW with a poor prognosis in patients with pancreatitis, mostly comparing patients with pancreatitis with patients without pancreatitis.…”
Section: Introductionmentioning
confidence: 99%